EUPHEMISMS IN JORDAN KLEPPER’S SEGMENTS ON THE DAILY SHOW YOUTUBE CHANNEL: A SEMANTIC APPROACH - Delima Prastika (LINGUISTICA, 2026)
This study aims to analyze euphemisms in Jordan Klepper's monologues on The Daily Show YouTube Channel using a semantic approach. This study analyzed transcripts from ten episodes broadcast between January and June 2025. The analysis process was carried out using a textual approach according to Smith (2017), and referring to the theory of types of euphemisms by Allan & Burridge (1991) and the theory of euphemism functions by Burridge (2012). The research found 34 euphemisms, divided into seven types. The most common type was "understatement," at 26.5%, followed by "flippancy" at 23.5%, and "figurative expression" at 17.6%.Based on their function, ludic euphemisms appeared most dominant (50%), followed by provocative functions (29.4%). Meanwhile, no euphemisms were found to function coherently. These findings suggest that Klepper's use of euphemisms not only serves to soften speech but also serves as a semantic strategy to convey humor, provoke critical reflection, and strengthen the effectiveness of satirical communication in digital media.